Response to Cabazitaxel Beyond 20 Cycles in A Patient with Penile Metastasis of Prostate Cancer: A Case Report - Atag, Elif; Semiz, Huseyin Salih; Kazaz, Seher Nazli; Tuna, Emine Burcin; Ozdogan, Ozhan; Bozkurt, Ozan; Demir, Omer; Karaoglu, Aziz (Urology Journal, 2017)
Penile metastases are extremely rare events and generally occurs at a late stage of primary disease. They mostlyoriginate from prostate and bladder in the genitourinary tract. Penile metastases have a dismal prognosis and verylow survival rates. We report a case of penile metastasis in 70-year-old geriatric male patient with prostatic adenocarcinomawho was treated with cabazitaxel chemotherapy beyond 20 cycles with a good response and acceptableminimal toxicity.